Botella de Leyden como introducción a los capacitores - Castellanos Ortegon, Ingrid Yurani; Vija Suarez, Javier (Revista Científica, 2011)
It presents a historical account of the Leyden jar, and start highlighting their historical context in which it was discovered, and the developments that have taken up to the modern capacitors with some of the most important applications in the field of engineering. The Leyden jar recreated as a device with some of its important calculations such as capacitance, which, lets be a teaching tool, since students have the opportunity to interact and understand its structure, functioning and physical phenomenology within an experimental approach.